Effect of thermoplastic veils on interlaminar fracture toughness of a glass fiber/vinyl ester composite. Issue 11 (15th October 2015) - Del Saz‐Orozco, Belén; Ray, Dipa; Stanley, Walter F.
Abstract : The effects of two thermoplastic micro‐veils, polyamide (PA) and polyethylene terephthalate (PET) veil, on the interlaminar fracture toughness of a glass fiber/vinyl ester (GF/VE) composite were investigated. The veils incorporated into the composite as interleaving materials were first characterized via scanning electron microscopy (SEM), differential scanning calorimetry (DSC), contact angle and tensile testing in order determine the best candidate as toughening agent for the GF/VE composite. Composite laminates were manufactured by vacuum‐assisted resin infusion process. Double cantilever beam (DCB) testing was performed to investigate the Mode I type interlaminar fracture toughness of the composites, which was characterized by critical strain energy release rate ( G IC ). An increased G IC was obtained by incorporating the PA veil, but it changed negligibly by the addition of the PET veil. The analysis of the composites fracture surface via SEM revealed increased fiber bridging between adjacent plies in the case of PA veil interleaved composites which played a key role in enhancing the Mode I interlaminar fracture toughness. However, the PET veil present in the interlaminar region did not take part in any energy absorbing mechanism during the delamination, thus keeping the G IC of the composite unaltered. POLYM. COMPOS., 38:2501–2508, 2017. © 2015 Society of Plastics Engineers